Early onset high grade dysplasia in ulcerative colitis. Issue 747 (January 1988) - Clements, D.; Suarez, V.; Thompson, H.; Alexander-Williams, J.; Allan, R. N.
Abstract : We report a patient with ulcerative colitis who underwent colectomy when aged 25 years for multifocal high grade dysplasia which had developed within 2 years of diagnosis, and only 5 1/2 years after his first symptoms. The implications of this case for the management of ulcerative colitis are discussed.